Strategi Proses Handover Pupuk dari Gudang ke Moda Transportasi Darat dalam Pencegahan Kerusakan Kantong Pupuk di PT Pupuk Sriwidjaja (Pusri) Palembang - Nahdah Iryani; Arianis Chan; Rani Sukmadewi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The distribution process is, of course, closely related to transport, as transport acts as a means of movement or delivery from the warehouse to the destination. PT Pupuk Indonesia is the largest fertiliser producer in Asia and is the official fertiliser producer. PT Pupuk Sriwidjaja (Pusri) Palembang is part or group of PT Pupuk Indonesia. PT Pupuk Sriwidjaja (Pusri) carries out deliveries by land and sea transport. PT Pupuk Sriwidjaja (Pusri) only uses trucks as land transport equipment to distribute fertiliser, so this research will focus on truck transport. The purpose of this research is to identify the strategies used by companies to prevent product damage during the transfer process from warehouse to land transport. The research method used is a qualitative method with a descriptive approach and the research design is a case study of the handover process. The outcome of this research is to find out the problems during the handover process, namely loss of fertilizer, shrinkage of fertilizer, damage to fertilizer bags such as bag leaks and deformed bags due to dirt. Also find out what strategies the company has in place to prevent product damage.